Factors Associated With Failure of Health System Reform: A Systematic Review and Meta-synthesis - Mahboubeh Bayat; Tahereh Kashkalani; Mahmoud Khodadost; Azad Shokri; Hamed Fattahi; Faeze Ghasemi Seproo; Fatemeh Younesi; Roghayeh Khalilnezhad (Korean Society for Preventive Medicine, 2023)
Objectives The health system reform process is highly political and controversial, and in most cases, it fails to realize its intended goals. This study was conducted to synthesize factors underlying the failure of health system reforms. Methods In this systematic review and meta-synthesis, we searched 9 international and regional databases to identify qualitative and mixed-methods studies published up to December 2019. Using thematic synthesis, we analyzed the data. We utilized the Standards for Reporting Qualitative Research checklist for quality assessment. Results After application of the inclusion and exclusion criteria, 40 of 1837 articles were included in the content analysis. The identified factors were organized into 7 main themes and 32 sub-themes. The main themes included: (1) reforms initiators' attitudes and knowledge; (2) weakness of political support; (3) lack of interest group support; (4) insufficient comprehensiveness of the reform; (5) problems related to the implementation of the reform; (6) harmful consequences of reform implementation; and (7) the political, economic, cultural, and social conditions of the society in which the reform takes place. Conclusions Health system reform is a deep and extensive process, and shortcomings and weaknesses in each step have overcome health reform attempts in many countries. Awareness of these failure factors and appropriate responses to these issues can help policymakers properly plan and implement future reform programs and achieve the ultimate goals of reform: to improve the quantity and quality of health services and the health of society.